Medium-low Speed Maglev Train Control and Network System - SU Ai-jun; YUAN Wen-ye; XU Yi-jing; LI Yi-ye; HE Wen-hui (机车电传动)
Design and configuration of network control system for medium-low speed maglev train were presented. Network control system was described from system bus, topology, and functions, etc. With analysis of logical vehicle control module and train line, mediumlow speed maglev train hard-wire relay control system was indicated.